2007
DOI: 10.1016/j.yebeh.2007.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ ratings of the academic performance of children with epilepsy

Abstract: The present study examined how knowledge of children's seizure condition was related to teachers' assessment of the children's academic ability. Children with epilepsy were divided into two groups based on teacher awareness of the child's seizure condition (Label). The children's achievement was assessed using the Woodcock Johnson Tests of Achievement-Revised (WJ-R), and the teacher's ratings were obtained from the Child Behavior Checklist Teacher Report Form (TRF) (Source). A 2 (Source) × 2 (Label) mixed-desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The effects may be similar to other types of labeling, such as children regarded as having learning or neurodevelopmental difficulties, and may become perpetuated over time, resulting in lower adult expectations for the child and reduced access to opportunities. 32 For many children, there may also be mislabeling, with the identified attentional and hyperactivity problems mimicking or overshadowing other learning or behavioral difficulties that might be better addressed in their own right. However, our study does not illuminate how teachers assimilated the identification information and how this was used or possibly shared with parents.…”
Section: The Role Of Labelingmentioning
confidence: 99%
“…The effects may be similar to other types of labeling, such as children regarded as having learning or neurodevelopmental difficulties, and may become perpetuated over time, resulting in lower adult expectations for the child and reduced access to opportunities. 32 For many children, there may also be mislabeling, with the identified attentional and hyperactivity problems mimicking or overshadowing other learning or behavioral difficulties that might be better addressed in their own right. However, our study does not illuminate how teachers assimilated the identification information and how this was used or possibly shared with parents.…”
Section: The Role Of Labelingmentioning
confidence: 99%
“…Dunn et al further discovered higher Total Behavior Problems scores in children with epilepsy who were being treated with an antiepileptic medication. Katzenstein, Fastenau, Dunn, and Austin (2007) discovered that simply having the label of epilepsy also influences teacher ratings. They found that children who were labeled as having epilepsy were more likely to have lower ratings of behavioral problems on the TRF.…”
mentioning
confidence: 99%
“…These impairments enhance learning difficulties (Elliot et al, 2005;Selassie et al, 2008;Williams, 2003), and negatively affect self-esteem (Caplan et al, 2006). Academic underachievement is also prominent among children with epilepsy (for example, Fastenau et al, 2008;Katzenstein, Fastenau, Dunn & Austin, 2007;Selassie et al, 2008;Wirrell et al, 2008) and is persistent over time (Austin et al, 1999). Difficulties in mathematics (Wirrell et al, 2008), spelling, writing, reading, reading comprehension (Aldenkamp et al, 2005;Berg et al, 2008;Moffat et al, 2009;Seidenberg, Beck, Geisser, Giordani, Sackellares, Berent, Dreifuss & Boll, 1986;Williams, 2003) and expressive language (Selassie et al, 2008) have been identified in the literature.…”
Section: Academic Domainmentioning
confidence: 99%